Effects of biochar on cadmium (Cd) uptake in vegetables and its natural downward movement in saline-alkali soil. Issue 1 (1st January 2020) - Sun, Jianxiong; Fan, Qinya; Ma, Jingwen; Cui, Liqiang; Quan, Guixiang; Yan, Jinlong; Wu, Limin; Hina, Kiran; Abdul, Basit; Wang, Hui
ABSTRACT: The focus was to assess the effects of biochar on Cd uptake by various vegetables and its downward movement in saline-alkali soil and carried out in polluted pots experiment. The results showed that the biomass of vegetables increased significantly by 16.9% to 519.9% while the Cd concentration in green pepper and eggplant fruits was decreased by 6.8% to 11.5% and 15.1% to 15.4% with the biochar application. The Cd in contaminated soil profile was transferred from topsoil (0-6 cm) to subsoil (6-12 cm) that was observed as 14.30 ± 4.17 mg kg -1 . The concentrations of Cd in soil with different fractions like exchangeable, reducible and oxidizable and the Cd uptake by vegetables were reduced. The release of residual Cd was decreased by 0.3 to 20.1% over time with biochar application (0-12 cm). The biochar was effective in mitigating the soil Cd pollution by preventing the vertical Cd leaching.